MO856IMPACT OF HEMODIALYSIS TIME PROLONGATION ON BLOOD PRESSURE CONTROL IN PREVALENT HEMODIALYSIS PATIENTS. (29th May 2021) - Teama, Nahla; Elsharabasy, Reem; Soliman, Heba; ElSharkawy, Magdy
Abstract: Background and Aims: Hypertension prevalence among ESRD patients range from 76% to 90%. Sodium & volume overload is among the main mechanisms. Increasing theduration of dialysis time, either by longer session hours or increased sessions, aiming at reducing the dry weight to achieve euvolemia, may be beneficial for individuals who failed to achieve target BP or ideal volume status during standard HD prescription hours.We aim to study the effect of increasing hemodialysis session time on blood pressure control. Method: This observational study was conducted on 50 adult clinically stable hypertensive prevalent HD patients on thrice weekly maintenance HD. Patients with secondary causes of hypertension and Patients with decompensated medical conditions were excluded from our study.Patients were divided into 2 groups:(A) 25 patients who received longer session hemodialysis session (4.5hour) and (B) 25 patients HD who received the usual 4 hours session. Revision of antihypertensive medications&dosages, dry weight was reassessed regularly, andthey were instructed to restrict their salt intake as much as possible aiming at BP <140/90mmHg.they werefollowed up for a period of 6 months assess changes of pre-dialysis blood pressure to monitor response. Results: Patients in both groups were age matched, with male sex predominance (64%in groupA&56% in groupB). Patients in both groups underwent their HD sessions mostly through AVF (68% and 92% for group A and B respectively). Ultrafiltration volume declined significantly with longer HD sessions compared to conventional sessions (p-value <0.001 vs 0.523). Longer HD session time session was associated with highly significant decline in mean SBP, (p-value <0.001). Longer HD session time session was associated with highly statistically significant decline in mean DBP, (p-value <0.001). The decline in mean perdialysis SBP & DBP was -17.27 &-9 mmHg, respectively and the rate of decline of postdialysis SBP & DBP was -6.45 & -12.38 mmHg, respectively at 6th month compared to values in 1st month of follow up period. Conclusion: Longer HD session duration is associated with better improvement in UF volume, mean SBP&DBP, pre-dialysis SBP&DBP and post-dialysis SBP&DBP as well.